RETRACTED: Perspectives on the application of IT in education to promote environmental education and sustainable development - Aslanova Alexandra; Kozubenko Anna; Alikhadzhiev Saidmagomed (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001